Efektivitas Ekstrak Kulit Manggis sebagai Upaya Mempercepat Penyembuhan Luka Perinium pada Ibu Postpartum - Amalia, Waifti; Danur Jayanti, Nicky; Indah Mayasari, Senditya (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
Perineal wounds in postpartum mothers carry a high risk of infection, which can delay healing and increase maternal mortality rates. The use of natural ingredients such as mangosteen peel (Garcinia mangostana Linn), known for its antibacterial and anti-inflammatory properties, has potential to accelerate wound healing. The goal is to find out if postpartum moms may speed up the healing of perineal wounds with a mangosteen peel decoction.  Using a one-group pre- and post-test strategy, this research used a pre-experimental design.  Fifteen women evaluated at TPMB Dhillah Shobirin Malang after giving birth and suffering from second-degree perineal lesions made up the sample. The intervention involved using mangosteen peel decoction for perineal cleansing three times daily for one week. Data were analyzed using the Wilcoxon Sign Rank Test. Before the intervention, all respondents (100%) experienced delayed wound healing (>14 days). After the intervention, 86.7% experienced rapid healing (1–6 days) and 13.3% experienced normal healing (7–14 days). Statistical analysis showed a significance value of 0.001 (p < 0.05), indicating a significant difference before and after the intervention. The mangosteen peel decoction is effective in accelerating perineal wound healing in postpartum mothers. This study recommends the utilization of mangosteen peel as a complementary therapy for postpartum wound care.